The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1021/es0206285
|View full text |Cite
|
Sign up to set email alerts
|

Nucleophilic Aliphatic Substitution Reactions of Propachlor, Alachlor, and Metolachlor with Bisulfide (HS-) and Polysulfides (Sn2-)

Abstract: Reactions of bisulfide and polysulfides with alachlor, propachlor, and metolachlor were examined in aqueous solution to investigate the role reduced sulfur species could play in effecting abiotic transformations of chloroacetanilide herbicides. Experiments at 25 degrees C demonstrated that reactions were approximately first-order in HS- concentration and revealed that polysulfides are considerably more reactive than HS-. delta H not equal to values for reactions of the three chloroacetanilides with HS- are sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
83
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(93 citation statements)
references
References 41 publications
(47 reference statements)
10
83
0
Order By: Relevance
“…The bisulfide is a strong nucleophile and can result metolachlor an efficient transformation rate, in which the complete transformation was achieved at the reaction time of 28 days in the presence of 3 mM bisulfide, with the pseudo-first-order kinetic constant value k of 0.112 AE 0.0082 days À1 (R 2 ¼ 0.970). The efficient transformations of chloroacetanilide herbicides, including metolachlor, by bisulfide were also reported in the previous report [13]. However, the transformation rate of metolachlor in our study was significantly higher than that reported by Loch et al [13], with the calculated second order rate constant of 1.0 Â 10 À2 M À1 s À1 compared with 0.25 Â 10 À2 M À1 s À1 , which may resulted from the reaction systems with different buffer solution for formation rate of bisulfide from Na 2 S.…”
Section: Metolachlor Transformation By Bisulfide On Aluminassupporting
confidence: 78%
See 3 more Smart Citations
“…The bisulfide is a strong nucleophile and can result metolachlor an efficient transformation rate, in which the complete transformation was achieved at the reaction time of 28 days in the presence of 3 mM bisulfide, with the pseudo-first-order kinetic constant value k of 0.112 AE 0.0082 days À1 (R 2 ¼ 0.970). The efficient transformations of chloroacetanilide herbicides, including metolachlor, by bisulfide were also reported in the previous report [13]. However, the transformation rate of metolachlor in our study was significantly higher than that reported by Loch et al [13], with the calculated second order rate constant of 1.0 Â 10 À2 M À1 s À1 compared with 0.25 Â 10 À2 M À1 s À1 , which may resulted from the reaction systems with different buffer solution for formation rate of bisulfide from Na 2 S.…”
Section: Metolachlor Transformation By Bisulfide On Aluminassupporting
confidence: 78%
“…The efficient transformations of chloroacetanilide herbicides, including metolachlor, by bisulfide were also reported in the previous report [13]. However, the transformation rate of metolachlor in our study was significantly higher than that reported by Loch et al [13], with the calculated second order rate constant of 1.0 Â 10 À2 M À1 s À1 compared with 0.25 Â 10 À2 M À1 s À1 , which may resulted from the reaction systems with different buffer solution for formation rate of bisulfide from Na 2 S.…”
Section: Metolachlor Transformation By Bisulfide On Aluminassupporting
confidence: 78%
See 2 more Smart Citations
“…Because of this resistance to degradation, exploiting the reductive transformation of chloroacetanilides through nucleophilic substitution in soil has recently received considerable attention (Lippa et al 2004). Because of the high reducing potential and strong nucleophilic abilities, the sulfur compounds, such as biosulfate (Bian et al 2009), thiosulfate (Gan et al 2002;Cai et al 2007), and polysulfide (Loch et al 2002), have been reported to readily dehalogenate organic halogenated pollutants efficiently. Dithionite is a relatively inexpensive sulfur compound which has long been used extensively in industrial applications (de Carvalho and Schwedt 2002).…”
Section: Introductionmentioning
confidence: 99%